Microbial strains isolated from CO2-venting Kolumbo submarine volcano show enhanced co-tolerance to acidity and antibiotics - Mandalakis, Manolis; Gavriilidou, Asimenia; Polymenakou, Paraskevi N; Christakis, Christos A; Nomikou, Paraskevi; Medvecký, Matej; Kilias, Stephanos P; Kentouri, Maroudio; Kotoulas, Georgios; Magoulas, Antonios (Marine environmental research, 2019)
As ocean acidification intensifies, there is growing global concern about the impacts that future pH levels are likely to have on marine life and ecosystems. By analogy, a steep decrease of seawater pH with depth is encountered inside the Kolumbo submarine volcano (northeast Santorini) as a result of natural CO2 venting, making this system ideal for ocean acidification research. Here, we investigated whether the increase of acidity towards deeper layers of Kolumbo crater had any effect on relevant phenotypic traits of bacterial isolates. A total of 31 Pseudomonas strains were isolated from both surface- (SSL) and deep-seawater layers (DSL), with the latter presenting a significantly higher acid tolerance. In particular, the DSL strains were able to cope with H+ levels that were 18 times higher. Similarly, the DSL isolates exhibited a significantly higher tolerance than SSL strains against six commonly used antibiotics and As(III). More importantly, a significant positive correlation was revealed between antibiotics and acid tolerance across the entire set of SSL and DSL isolates. Our findings imply that Pseudomonas species with higher resilience to antibiotics could be favored by the prospect of acidifying oceans. Further studies are required to determine if this feature is universal across marine bacteria and to assess potential ecological impacts.
Keywords: Hydrothermal Vents; Ecosystem; Heavy metals; Extreme environments; Acidification; Submarine volcanoes; antibakteriální látky; Antibiotic/acid tolerance; Marine microbial ecology; Oceans and Seas; hydrotermální průduchy; Carbon Dioxide; Anti-Bacterial Agents; Seawater; Acids; Hydrogen-Ion Concentration; oxid uhličitý; Bacteria; koncentrace vodíkových iontů; oceány a moře; mořská voda; kyseliny; ekosystém; Pseudomonas